Harmoni dalam Keragaman Weton: Tradisi Perkawinan di Desa Kepuh Kembeng - Mohammad Shodiqin; Muhammad Jazil Rifqi (Institut Agama Islam Negeri Kerinci, 2025)
The weton tradition in Javanese culture remains a significant cultural heritage that influences marriage decisions in various communities, including in Kepuh Kembeng Village, Jombang. This study aims to analyze how local society responds to weton incompatibility in marriage and to what extent such cultural values affect their social life. The research employs a qualitative descriptive method, with data collected through observations and interviews involving community leaders, religious figures, and couples who experienced weton differences. The findings reveal that although weton is still respected, it is no longer viewed as an absolute barrier to marriage. Values of social harmony and collective deliberation serve as key social mechanisms that enable negotiation between cultural traditions and family interests. Using Talcott Parsons’ structural functionalism, the weton tradition is interpreted as a flexible symbolic system that functions to maintain social order rather than as a rigid normative constraint. This study contributes to the discourse on living law and enriches the understanding of the interplay between cultural tradition and religious values in contemporary Muslim Javanese society.